Der Weg zum KIT : von der jahrzehntelangen Zusammenarbeit des Forschungszentrums Karlsruhe mit der Universität Karlsruhe (TH) zur Gründung des Karlsruher Instituts für Technologie. Eine Darstellung nach den Aussagen von Zeitzeugen - Hartmann, MichaelNippert, Klaus [Hrsg.] (Veröffentlichungen aus dem Archiv des Karlsruher Instituts für Technologie, 2013)
The formation of the Karlsruhe Institute of Technology (KIT) is described as a longlasting process which made the partners in the merger of 2009 come closer since the beginning of the Nuclear Research Center at Karlsruhe in 1956. By the means of common chairs and institutes the Nuclear Research Center and the University of Karlsruhe made experiences seminal for the idea of KIT born and put into effect wihin the competition of excellency initated by the federal government and the federal states.